EFEKTIVITAS MEDIA INTERAKTIF BERBASIS WORDWALL PADA PEMBELAJARAN PENDIDIKAN PANCASILA ELEMEN KEBHINEKAAN DI KELAS III SEKOLAH DASAR. - Hasna Sabita, Alya; Reinita; Mansurdin; Waldi, Atri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of Wordwall-based interactive media in Pancasila Education learning on the diversity element for Grade III students of elementary school in Padang City. This research uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were Grade III students from three elementary schools: SDN 11 Pauh, SDN 02 Cupak Tangah, and SDN 13 Kapalo Koto. The effectiveness of the media was measured using pretest and posttest results analyzed through the N-Gain formula. The findings showed that the Wordwall-based interactive media was effective in improving student learning outcomes. At SDN 11 Pauh (pilot school), the average pretest score was 57.5, which increased to 84.5 in the posttest, with an N-Gain score of 0.59 (moderate/effective category). At SDN 02 Cupak Tangah (research school), the average pretest score was 60, rising to 88.70 in the posttest, with an N-Gain score of 0.734 (high/highly effective category). At SDN 13 Kapalo Koto (implementation school), the average pretest was 66.36, which increased to 89.09 in the posttest, yielding an N-Gain score of 0.637 (moderate/effective category). These results indicate that Wordwall interactive media successfully enhances students' learning achievement on the topic of ethnic and cultural diversity in Indonesia.